Adenosine A2A Receptor in Bone Marrow-Derived Cells Mediated Macrophages M2 Polarization via PPARγ-P65 Pathway in Chronic Hypoperfusion Situation - Mou, Ke-Jie; Shen, Kai-Feng; Li, Yan-Ling; Wu, Zhi-Feng; Duan, Wei (Frontiers in Aging Neuroscience, 2022)
Background: The role of adenosine A2A receptor (A2AR) in the ischemic white matter damage induced by chronic cerebral hypoperfusion remains obscure. Here we investigated the role of A2AR in the process of macrophage polarizations in the white matter damage induced by chronic cerebral hypoperfusion and explored the involved signaling pathways. Methods: We combined mouse model and macrophage cell line for our study. White matter lesions were induced in A2AR knockout mice, wild-type mice, and chimeric mice generated by bone marrow cells transplantation through bilateral common carotid artery stenosis. Microglial/macrophage polarization in the corpus callosum was detected by immunofluorescence. For the cell line experiments, RAW264.7 macrophages were treated with the A2AR agonist CHS21680 or A2AR antagonist SCH58261 for 30 min and cultured under low-glucose and hypoxic conditions. Macrophage polarization was examined by immunofluorescence. The expression of peroxisome proliferator activated receptor gamma (PPARγ) and transcription factor P65 was examined by western blotting and real-time polymerase chain reaction (RT-PCR). Inflammatory cytokine factors were assessed by enzyme-linked immunosorbent assay (ELISA) and RT-PCR. Results: Both global A2AR knockout and inactivation of A2AR in bone marrow-derived cells enhanced M1 marker expression in chronic ischemic white matter lesions. Under low-glucose and hypoxic conditions, CGS21680 treatment promoted macrophage M2 polarization, increased the expression of PPARγ, P65, and interleukin-10 (IL-10) and suppressed the expression of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). The CGS21680-induced upregulation of P65 and IL-10 was abolished in macrophages upon PPARγ knockdown. The downregulation of TNF-α and IL-1β by CGS21680 was less affected by PPARγ knockdown. Conclusions: In the cerebral hypoperfusion induced white matter damage, A2AR signaling in bone marrow-derived cells induces macrophage M2 polarization and increases the expression of the anti-inflammatory factor IL-10 via the PPARγ-P65 pathway, both of which might explain its neuroprotective effect.